1993
DOI: 10.1002/jca.2920080207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bioavailability of ferric polymaltose and ferrous sulphate in iron‐deficient blood donors

Abstract: Absolute iron deficiency is treated by correcting the causative lesion and then, traditionally, administering sufficient amounts of ferrous salt to return the haemoglobin level to normal and replenish body stores. The bioavailability of ferric compounds has been questioned and accordingly their therapeutic role remains controversial. A special problem is posed by regular blood donation, where the frequency of phlebotomy is limited by the haemoglobin level, which, in turn, requires maintenance of an adequate su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 36 publications
2
31
0
4
Order By: Relevance
“…Randomized studies in adults have confirmed a lower rate of gastrointestinal symptoms with IPC versus ferrous sulfate [8, 20, 27, 28]. In children, comparative data are more sparse, but there are reports of fewer gastrointestinal adverse events [12] and less frequent tooth staining [11] in IPC-treated children compared to those given ferrous sulfate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized studies in adults have confirmed a lower rate of gastrointestinal symptoms with IPC versus ferrous sulfate [8, 20, 27, 28]. In children, comparative data are more sparse, but there are reports of fewer gastrointestinal adverse events [12] and less frequent tooth staining [11] in IPC-treated children compared to those given ferrous sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Polynuclear preparations based on the ferric form of iron, such as iron hydroxide polymaltose complex (IPC), have been developed to improve tolerability. IPC provides similar iron bioavailability to ferrous sulfate [8] but has a stable structure that confers more controlled absorption of iron [9]. A recent meta-analysis [10] has confirmed that IPC and ferrous sulfate provide similar improvements in hemoglobin (Hb) levels in adult patients with iron deficiency anemia, but with superior tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…Less improvement was seen in anaemia in the group receiving the 100 mg (daily) Fe +3 polymaltose complex when compared to the other groups [17]. In 1994, Nielsen et al compared Fe +2 sulphate and the ferric-polymaltose complex and found that there was no significant change in the mean haemoglobin value in the group receiving the ferric-polymaltose.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11]18 As propriedades mencionadas anteriormente conferem à ferripolimaltose menor incidência de EA, proporcionando maior adesão ao tratamento e melhores resultados. [17][18][19] Estudos em animais têm demonstrado que o processo de oxidação necessário para a absorção dos sais ferrosos provoca geração de radicais livres e lesão celular, o que pode justificar o maior incremento dos níveis da ferritina nos pacientes tratados com sulfato ferroso. Entretanto, quando se analisa o incremento de ferritina tecidual, que é o que realmente interessa, esse aumento é maior para aqueles que recebem a ferripolimaltose que para os que recebem o sulfato ferroso.…”
Section: Complexo De Ferro Polimaltosado (Fe 3+ )unclassified
“…O estudo prospectivo controlado e randomizado mais importante é o de Jacobs et al, 19 que compararam a biodisponibilidade e bioequivalência da ferripolimaltose e do sulfato ferroso em candidatos à doação de sangue e recusados para tal procedimento devido ao diagnóstico de anemia ferropriva. Os autores utilizaram 120 mg de sulfato ferroso (60 mg 2x/dia, em jejum; n=51) versus 100 mg de ferripolimaltose no café da manhã (n=55) versus 200 mg de ferripolimaltose (100 mg no café e no jantar; n=53).…”
Section: Ferripolimaltose Versus Sais Ferrosos Ou Aminoqueladosunclassified